Physicochemical kinetic reactive transport modeling in quartz arenite: implications on geothermal potential - Bowman, Samuel; Barton, John; Pathak, Arkajyoti; Sharma, Shikha (Frontiers in Earth Science, 2026)
Kinetic reactive transport modeling has been performed on the quartz-dominant Tuscarora Sandstone. Physical parameters including temperature, porosity, and permeability, as well as chemical parameters including pH, dissolved ions, and mineral precipitation and dissolution have been explored as a function of flow rate. This approach has shown strong spatial relationships between fluid-rock interactions and flow, particularly with respect to extensive reservoir cooling. At 10 L/s, the reservoir is cooled to ∼75 °C after 50 years and is nearly entirely equilibrated with the working fluid at 30 L/s. There is a slight increase in porosity immediately near the injection well likely due to reservoir dissolution. Simulation results in the reservoir block model show negligible secondary mineral precipitation at all modeled injection rates. We suggest that the proposed model can be utilized in evaluating the geothermal potential of low porosity quartz arenite reservoirs by predicting spatial temperature variations as well as observed fluid-mineral assemblages in field settings.